Immediate Effect of Buteyko Breathing and Bhramari Pranayama on Blood Pressure, Heart Rate and Oxygen Saturation in Hypertensive Patients: A Comparative Study - Samiksha Sanjiv Sathe1, Tejal Rajandekar2, Kirti Thodge3, Amol Bhawane4, Utkarsh Thatere5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: There are studies showing the use of Buteyko breathing technique & Bhramari Pranayama in reducingcardiorespiratory parameters in normal healthy individuals but to the best of our knowledge there is hardlyany study that has reported comparative immediate effect of these two techniques. Thus the aim of our studywas to evaluate the immediate effect of these two techniques on Blood pressure, heart rate and SpO2 inHypertensive patients.Method: The research design used was Comparative Experimental study design. Total 52 participants werescreened and those meeting the inclusion criteria (n=42) were included in the study. The participants wererandomly divided into two groups- Buteyko breathing and Bhramari pranayama Group of 21 each. Pre andimmediate post intervention scores were measured in terms of systolic BP, Diastolic BP, heart rate and SpO2.Findings: Inter group comparison (student’s unpaired t test) showed that there was no statisticallysignificant difference between the two groups in terms of Systolic and Diastolic BP, Heart rate and SpO2.The comparison of pre and post intervention valuesof the outcome measures in Buteyko group showeda significant difference in Systolic BP, Heart rate and SpO2 values whereas in Bhramari group there wasstatistically significant difference only the in Systolic BP values.Conclusion: It can be concluded from the present study that Buteyko breathing and Bhramari pranayamaare equally effective in immediately reducing the systolic blood pressure in hypertensive patients.